2019
DOI: 10.1002/chem.201903852
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Aluminium Distribution in Small‐Sized ZSM‐5 Crystals during Desilication

Abstract: Hollow ZSM‐5 zeolites of size below one micrometer can be produced by desilication of crystals with aluminium zoning. The parent crystals have a core–shell structure: the core part has nearly no aluminium, whereas the aluminium content in the shell increases when extending to exterior surface. Transmission electron microscopy confirmed the preservation of the crystalline shell after base leaching, but could not identify its subtle change. An increase of the Si/Al ratio of the surface was detected upon leaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…337 and 342.2 eV, respectively, can be assigned to PdO (Figure i). The line width of the Pd 3d peak increased by increasing the photon kinetic energy due to a decrease in resolving power of the beamline monochromator . Despite that, the Pd 3d peak intensity did not change significantly in the whole photoelectron kinetic energy range, suggesting that the palladium oxide particles were relatively homogeneously distributed.…”
Section: Resultsmentioning
confidence: 97%
“…337 and 342.2 eV, respectively, can be assigned to PdO (Figure i). The line width of the Pd 3d peak increased by increasing the photon kinetic energy due to a decrease in resolving power of the beamline monochromator . Despite that, the Pd 3d peak intensity did not change significantly in the whole photoelectron kinetic energy range, suggesting that the palladium oxide particles were relatively homogeneously distributed.…”
Section: Resultsmentioning
confidence: 97%
“…For example, para -xylene selectivity can be enhanced by depositing amorphous or crystalline silica composition on the individual ZSM-5 crystals. , In fact, aluminum zoning is well-known for ZSM-5 crystals synthesized with tetrapropylammonium ions (TPA + ) as a template . Over micrometer-sized ZSM-5 crystals, aluminum zoning was visualized by synchrotron-based micro-X-ray diffraction and atomic probe tomography (APT). , Over nanosized crystals, aluminum zoning still exists, , and van Bokhoven et al recently observed that the nanosized ZSM-5 crystals had a core–shell structure, in terms of aluminum distribution . The core part had nearly no aluminum, whereas the aluminum content in the shell gradually increased when extending to the exterior surface.…”
Section: Discussionmentioning
confidence: 99%
“…392,393 Over nanosized crystals, aluminum zoning still exists, 308,394 and van Bokhoven et al recently observed that the nanosized ZSM-5 crystals had a core−shell structure, in terms of aluminum distribution. 395 The core part had nearly no aluminum, whereas the aluminum content in the shell gradually increased when extending to the exterior surface. One could think that such an uneven distribution of aluminum might promote the location of Zn species close to the Brønsted acid sites in the shell, which could have an effect on the catalytic process.…”
Section: ■ Summary and Outlookmentioning
confidence: 99%
“…While the NaZSM-5 molecular sieve has been widely applied because of its various and adjustable active centers and characteristic microporous structure, adjusting the Si/Al ratio of the NaZSM-5 framework and constructing hierarchical porous structures has been pursued to create suitable active centers, strengthen molecular diffusion, and enhance the reactivity and selectivity while simultaneously inhibiting catalyst deactivation. Among the previous modification strategies, the common route involves impregnation and desiliconization/dealumination in acidic or basic environments [ 39 , 40 , 41 , 42 , 43 , 44 ]. ZrO 2 is a transition metal oxide with both acidic and basic properties [ 45 , 46 , 47 , 48 , 49 ], in which its monoclinic (m) and tetragonal (t) crystalline phases can be used as catalysts or carriers.…”
Section: Introductionmentioning
confidence: 99%